Improving resilience of islanding protection - implementation of a Q-f droop for inverter-based generation - Kent, M. A.; Peebles, A. S.; Williams, S. J.; Hendry, R.; Kemp-Garcia, R. C.; Dysko, A. (19th International Conference on AC and DC Power Transmission (ACDC 2023), 2023)
As the prevalence of distributed generation (DG) continues to increase in the GB network, anti-islanding protection has been the subject of industry focus, with work done to alter the existing Rate of Change of Frequency (ROCOF) settings. However, there are still concerns regarding the resilience and security of this method based upon non-detection zones (NDZ), and the potential of system-wide events and network faults leading to nuisance tripping. This paper provides a review of the theory and literature, exploring the issues with power system islanding and the current anti-islanding protection methods. A novel protection method, based on a reactive power - frequency (Q-f) droop, is developed and implemented into a Simulink inverter-connected DG model, to test under various distribution network scenarios including islanding and system-wide frequency excursions. This new method was compared to the existing ROCOF method and showed improved performance in all network scenarios studies. The Q-f droop method had no NDZ and was developed to be customisable for a range of network regulation requirements. Finally, aspects of the method such as multi-DG operation, financial and practical implications have been explored.